Histopathological And Immunohistochemical Analysis Of Testicular Tissues Of Wistar Rats Exposed To A High-Fat Diet - Krishna B, Ashwin; Murthykumar, Karthikeyan (Journal of Neonatal Surgery, 2024)
INTRODUCTION: Histopathology is the study of the signs of the disease using the microscopic examination of a biopsy or surgical specimen that is processed and fixed onto glass slides. Histochemistry is an important technique that is used for the visualization of biological structures. A high-fat diet (HFD) is a diet consisting of at least 35% of total calories consumed from fats, both unsaturated and saturated. AIM: To elucidate Histopathological and immunohistochemical analysis of testicular tissues of wistar rats exposed to high fat diet. MATERIALS AND METHODS: Healthy adult male albino Wistar rats were maintained under standard laboratory conditions with ad libitum access to food and water, in accordance with Institutional Animal Ethics Committee guidelines (IAEC no: BRULAC/SDCH/SIMATS/IAEC/02-2019/015). The animals were divided into two experimental groups: Group 1 (n = 2): Subjected to death by submersion in water. Group 2 (n = 4): Clinically sacrificed as controls. Following a 72-hour post-mortem interval, skin and epithelial tissues from both groups were collected and analyzed. RESULTS: There is an Increased lipid deposition when compared to control group. There is narrowing of seminiferous tubules. Significant Reduction in cellular proliferation. Cell shrinkage is also seen. CONCLUSION: We have identified several candidate proteins and conducted pathway analysis around the effects of the HF diet on the testis providing novel insights which are not previously described....